2018
DOI: 10.1111/jth.14245
|View full text |Cite
|
Sign up to set email alerts
|

Heparin–protamine balance after neonatal cardiopulmonary bypass surgery

Abstract: Background Neonates undergoing cardiopulmonary bypass (CPB) are at risk of excessive bleeding. Blood is anticoagulated with heparin during CPB. Heparin activity is reversed with protamine at the end of CPB. Paradoxically, protamine also inhibits blood coagulation when it is dosed in excess of heparin. Objectives To evaluate heparin-protamine balance in neonates undergoing CPB by using research and clinical assays, and to determine its association with postoperative bleeding. Patients/Methods Neonates undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
9
0
3
Order By: Relevance
“…These included measures of coagulation function such as hematocrit, fibrinogen level, prothrombin time, or partial thromboplastin time, as was also reported previously. 52 Unique to this study is the report that platelet count and platelet responses to stimulation with agonists that activate platelets through the thromboxane A2, thrombin, collagen, or P2Y 1 and P2Y 12 receptors also did not differ significantly between patients who bled excessively and those who did not. Platelet responses to epinephrine and ristocetin, which activate platelets through the α 2 -adrenergic and GPIb/IX/V receptors, respectively, were also tested in this study but found to be too low to allow for meaningful comparisons (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…These included measures of coagulation function such as hematocrit, fibrinogen level, prothrombin time, or partial thromboplastin time, as was also reported previously. 52 Unique to this study is the report that platelet count and platelet responses to stimulation with agonists that activate platelets through the thromboxane A2, thrombin, collagen, or P2Y 1 and P2Y 12 receptors also did not differ significantly between patients who bled excessively and those who did not. Platelet responses to epinephrine and ristocetin, which activate platelets through the α 2 -adrenergic and GPIb/IX/V receptors, respectively, were also tested in this study but found to be too low to allow for meaningful comparisons (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…Numerous studies have evaluated CAT as a predictor of bleeding in adults [54,55], but few have in neonates. Peterson et al found that CAT did not predict post-operative bleeding after cardiopulmonary bypass (CPB) [40]. Tripodi et al found no difference in ETP measurements at birth, between VLBW infants that developed an IVH and those that did not [9].…”
Section: Cat As a Predictor Of Clinical Bleeding In Neonatesmentioning
confidence: 99%
“…Haidl et al centrifuged whole blood at 200 × g for 10 min and diluted this with PPP to produce a specific platelet count (10, 50, 75 and 100 × 10^9/L) [ 25 ]. Peterson et al centrifuged whole blood at 100 × g for 10 min, before diluting with PPP to achieve a standard platelet count of 50 × 10^9/L [ 40 ]. Bernhard et al pelleted and washed platelets, before re-suspending them in PPP and adjusting “to similar counts” [ 38 ].…”
Section: Evaluating the Effect Of Neonatal Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma TFPIα levels promptly increase ≈2-to 4-fold following infusion of unfractionated or low-molecular-weight heparin into adults 26,27 or neonates. 28 Heparin-releasable TFPIα is also present in cultured human endothelial cells. 29,30 Heparin-releasable TFPIα and endothelial bound TFPIβ maintain anticoagulant properties of the vasculature.…”
mentioning
confidence: 99%